Pengaruh Kompetensi SDM, Partisipasi Masyarakat dan SPI terhadap Akuntabilitas Pengelolaan Keuangan Dana BOS di SMA/SMK Negeri di Kota Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze in more depth the influence of human resource (HR) competency, community participation, and internal control systems on the accountability of School Operational Assistance (BOS) Fund financial management at public senior high schools (SMA) and vocational high schools (SMK) in Kupang City. The background to this study is based on the large allocation of BOS Funds at the SMA/SMK level, which requires transparent, accountable, effective, efficient, and participatory management to achieve the goal of improving educational quality. BOS Funds are public funds whose use must be accounted for to the government and the public. Therefore, professional financial management is required, taking into account manager competency, stakeholder involvement, and the implementation of an adequate internal control system. The study used a quantitative approach with a descriptive approach. Primary data were obtained through questionnaires distributed to principals, treasurers, BOS team members, and related parties at public senior high schools (SMK) in Kupang City. Data analysis was conducted using multiple linear regression techniques to test the partial and simultaneous effects between variables. The results of the study indicate that (1) human resource competency has a positive and significant impact on the accountability of the BOS Fund financial management because human resources with adequate knowledge, skills, and experience are able to plan, implement, and evaluate the use of funds appropriately; (2) community participation has a positive impact on accountability through active involvement in the preparation of the RKAS (Work Plan and Budget), program implementation, and supervision; (3) the internal control system has a positive impact on accountability by ensuring clear procedures, preventing irregularities, and complying with regulations; and (4) all three variables simultaneously have a significant impact on the accountability of the BOS Fund financial management. These findings emphasize the importance of improving manager competency, encouraging community participation, and optimizing the internal control system so that the BOS Fund can be utilized effectively to improve the quality of education in Kupang City's public high schools (SMA) and vocational high schools (SMK).